Calculation of Resonating Frequency of an Equilateral Triangular Microstrip Antenna Using Artificial Neural Network, “This paper has been withdrawn” - Gupta, Prachi; Singhal, P.K.; Gupta, Ritambhra (International Journal of Engineering and Technology, 2012)
This paper has been withdrawn.